THE INFLUENCE OF ATTITUDES, SUBJECTIVE NORMS, AND BEHAVIOURAL CONTROL ON THE BUYING INTEREST OF UNY MALE STUDENTS IN FAST FASHION PRODUCTS - Laila Nurul Himmah; Chytra Mahanani; Resi Sepsilia Elvera; Moh. Adam Jerusalem (Sean Institute, 2023)
The development of the fashion industry in Indonesia background this research. The purchase of fast fashion products at affordable prices has become common in modern society, one of which is students as part of self-essentialization efforts, thus making behaviour consumptive. This study aims to test the influence of attitudes, subjective norms and behavioural control on the buying interest of UNY male students in fast fashion products. Data collection techniques using online questionnaires. The sample selection technique used stratified random sampling and obtained 30 respondents of UNY male students from various faculties. Data analysis techniques use multiple regression analysis using SPSS. The results of this study show that the attitude variable significantly influences the buying interest of UNY male students in fast fashion products (β = 0.438, p < 0.05). The subjective norm variable significantly influences the buying interest of UNY male students in fast fashion products (β = 0.373, p < 0.05). As well as behavioural control variables significantly affect the buying interest of UNY male students in fast fashion products (β = 0.461, p < 0.05). And the variables Attitude, Subjective norm, and Perceived Behaviour Control jointly significantly influenced the buying interest of UNY male students in fast fashion products (R² = 0.368, F-hit = 6,024, p < 0.05). This research provides benefits to increase understanding of fast fashion products.